Pretomanid is a dual inhibitor of the cytochrome bcc:aa3 and cytochrome bd oxidase that synergizes with Q203 to eradicate Mycobacterium tuberculosis - Nurlilah Ab Rahman (Nanyang Technological University, 2022)
Tuberculosis is a global disease that carries with it high health and socio-economic burdens onto populations. Millions of people come down with the active form of the disease every year but the proportion of the world population that carries the latent form of this disease is believed to around twenty-five percent as per the 2021 report by the World Health Organization. Tuberculosis disproportionately affects populations across ages, genders and geographical regions although the South-east Asia region accounts for almost half of all reported cases in 2020. Additionally, the increased incidences and spread of TB-HIV dual infections worldwide and the ongoing COVID-19 pandemic have introduced setbacks in the World Health Organization’s plan to diagnose, treat and eradicate TB disease by 2030. Although the introduction of new drugs and vaccine candidates into the TB pipeline has been slow, progress and improvements in TB treatments for patients have increased over the years. Patients afflicted with drug-susceptible tuberculosis are started out with a panel of up to four first-line drugs over a period of six months. Often, regimens would have to be adjusted to swap drugs with others or include those from the second-line panel due to patients’ medical contraindications, low-adherence to treatment or the emergence of resistance, a phenomenon of increasing concern and importance over the years. Bacterial persistence is attributed to the formation of heterogeneous drug- susceptible and resistant sub-populations as the bacilli navigate the harsh changes in the microenvironments at localized infection sites in order to ensure long-term survivability. This heterogeneity has been reported to be one of the factors associated with TB treatment failures. There have been many studies conducted to study the biomechanism behind bacterial persistence to exploit weaknesses within the processes over the years, with results guiding the use of existing anti-TB drugs and the development of new TB drugs and the design of TB drug treatments. One of the processes attributed to persistence is the downregulation of mycobacterial metabolism guided by the oxidative phosphorylation (OxPhos) pathway. The OxPhos pathway is involved in the generation of adenosine triphosphate (ATP), the main energy currency in the cell and it presents many points of susceptibilities that can be exploited during TB drug development. This Thesis investigated the impact of two clinically important drugs, Q203 and Pretomanid, on the OxPhos pathway and the efficacy of this two-drug combination on replicating and non-replicating cells. This Thesis demonstrates very promising data for this drug combination on both bacteria populations and discusses the viability of implementing the combination into the TB drug pipeline.